ANALISIS PEMEROLEHAN BAHASA DAN PEMBELAJARAN BAHASA PADA ANAK USIA SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine how elementary school-aged children acquire and learn language, and to identify factors that influence this language learning process. The method used in this study is a literature study, namely by collecting and analyzing various written materials such as journals, books, scientific articles, and related supporting documents. The results of the study indicate that language learning is a natural process that begins in childhood, through how children interact with their surroundings, especially in acquiring a first language. Meanwhile, language learning is a conscious, structured, and formal process, generally occurring in the school environment in an effort to master a second language. Factors that influence how someone acquires and learns a language include the surrounding environment, how parents use the first language, the child's physical and biological condition, and the type of social guidance provided by the family and school. The findings also indicate that an imbalance between how children learn their first language and the process of learning a second language can cause obstacles in the development of their language skills. Therefore, cooperation between the family and school environment is necessary for children's language development to be achieved properly.